The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Brain natriuretic peptide for prevention of contrast-inducednephropathy: a meta-analysis of randomized controlled trials - Xue-biao Wei; Lei Jiang; Xin-rong Liu; Dan-qing Yu; Ning Tan; Ji-yan Chen; Ying-ling Zhou; Peng-cheng He; Yuan-hui Liu (European Journal of Clinical Pharmacology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Plasma Oxytocin and Arginine-Vasopressin Levels in Children with Autism Spectrum Disorder in China: Associations with Symptoms - Hong-Feng Zhang; Yu-Chuan Dai; Jing Wu; Mei-Xiang Jia; Ji-Shui Zhang; Xiao-Jing Shou; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2016)

Erratum to: The intracellular carboxyl tail of the PAR-2 receptor controls intracellular signaling and cell death - Zhihui Zhu; Rolf Stricker; Rong yu Li; Gregor Zündorf; Georg Reiser (Cell and Tissue Research, 2016)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

Dietary Guidelines for Chinese Residents (2016): comments and comparisons - Shan-shan Wang; Sovichea Lay; Hai-ning Yu; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2016)

A bioeroding foraminifer, Hyrrokkin sarcophaga, on deepwater corals from the South China Sea - Yu-Rong Cheng; Chang-Feng Dai (Coral Reefs, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

The LXR ligand GW3965 inhibits Newcastle disease virus infection by affecting cholesterol homeostasis - Xiang-xiang Sheng; Ying-jie Sun; Yuan Zhan; Yu-rong Qu; Hua-xia Wang; Miao Luo; Ying Liao; Xu-sheng Qiu; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2016)

Combinatorial anticancer effects of curcumin and sorafenib towards thyroid cancer cells via PI3K/Akt and ERK pathways - Junjia Zhang; Jichun Yu; Rong Xie; Wanzhi Chen; Yunxia Lv (Natural Product Research, 2016)

Strawberry MOTHER OF FT AND TFL1 regulates seed germination and post-germination growth through integrating GA and ABA signaling in Arabidopsis - Yang Hu; Yu-Rong Gao; Wei Wei; Kai Zhang; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

High-level expression of a novel recombinant human plasminogen activator (rhPA) in the milk of transgenic rabbits and its thrombolytic bioactivity in vitro - Shaozheng Song; Xin Ge; Yaobin Cheng; Rui Lu; Ting Zhang; Baoli Yu; Xueqiao Ji; Zhengqiang Qi; Yao Rong; Yuguo Yuan; Yong Cheng (Molecular Biology Reports, 2016)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

Molecular characterization, expression and methylation status analysis of BMP4 gene in skin tissue of Liaoning cashmere goat during hair follicle cycle - Wen L. Bai; Yun L. Dang; Jiao J. Wang; Rong H. Yin; Ze Y. Wang; Yu B. Zhu; Yu Y. Cong; Hui L. Xue; Liang Deng; Dan Guo; Shi Q. Wang; Shu H. Yang (Genetica, 2016)

Steroidobacter flavus sp. nov., a microcystin-degrading Gammaproteobacterium isolated from soil - Zhi-Lian Gong; Chang-Feng Zhang; Rong Jin; Yu-Qin Zhang (Antonie van Leeuwenhoek, 2016)

Short-term variability in the dates of the Indian monsoon onset and retreat on the southern and northern slopes of the central Himalayas as determined by precipitation stable isotopes - Wusheng Yu; Tandong Yao; Lide Tian; Yaoming Ma; Rong Wen; Lochan P. Devkota; Weicai Wang; Dongmei Qu; Tek B. Chhetri (Climate Dynamics, 2016)

Long-Acting Phospholipid Gel of Exenatide for Long-Term Therapy of Type II Diabetes - Mei Hu; Yu Zhang; Nanxi Xiang; Ying Zhong; Tao Gong; Zhi-Rong Zhang; Yao Fu (Pharmaceutical Research, 2016)

The association between the ring finger protein 213 (RNF213) polymorphisms and moyamoya disease susceptibility: a meta-analysis based on case–control studies - Xun-Sha Sun; Jun Wen; Jiao-Xing Li; Rong Lai; Yu-Fang Wang; Hui-Jiao Liu; Wen-Li Sheng (Molecular Genetics and Genomics, 2016)

Evaluation of the major royal jelly proteins as an alternative to fetal bovine serum in culturing human cell lines - Di Chen; Xiao-xuan Xin; Hao-cheng Qian; Zhang-yin Yu; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2016)

Molecularly imprinted polymers as the extracted sorbents of clenbuterol ahead of liquid chromatographic determination - Sovichea Lay; Hai-ning Yu; Bao-xiang Hu; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2016)

Prenatal low-level mercury exposure and infant neurodevelopment at 12 months in rural northern China - Yi Hu; Limei Chen; Caifeng Wang; Yijun Zhou; Yan Zhang; Yiwen Wang; Rong Shi; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2016)

Pantoea hericii sp. nov., Isolated from the Fruiting Bodies of Hericium erinaceus - Chengbo Rong; Yuanwei Ma; Shouxian Wang; Yu Liu; Sanfeng Chen; Bin Huang; Jing Wang; Feng Xu (Current Microbiology, 2016)

The strong El Niño of 2015/16 and its dominant impacts on global and China's climate - Panmao Zhai; Rong Yu; Yanjun Guo; Qingxiang Li; Xuejuan Ren; Yaqiang Wang; Wenhui Xu; Yanju Liu; Yihui Ding (Journal of Meteorological Research, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Improving the antioxidant activity and enriching salvianolic acids by the fermentation of Salvia miltiorrhizae with Geomyces luteus - Yun Xing; Le Cai; Tian-peng Yin; Yang Chen; Jing Yu; Ya-rong Wang; Zhong-tao Ding (Journal of Zhejiang University-SCIENCE B, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

The influence of plant root system architectural properties upon the stability of loess hillslopes, Northeast Qinghai, China - Jiang-tao Fu; Xia-song Hu; Gary Brierley; Na Qiao; Qin-qin Yu; Hai-jing Lu; Guo-rong Li; Hai-li Zhu (Journal of Mountain Science, 2016)

Bacterial community dissimilarity between the surface and subsurface soils equals horizontal differences over several kilometers in the western Tibetan Plateau - Haiyan Chu; Huaibo Sun; Binu M. Tripathi; Jonathan M. Adams; Rong Huang; Yangjian Zhang; Yu Shi (Environmental Microbiology, 2016)
Summary Many studies have investigated patterns in the near‐surface soil microbial community over large spatial scales. However, less is known about variation in subsurface (15–30 cm of depth) microbial communities. Here we studied depth profiles of microbial communities in high‐elevation soils from Tibet. The relative abundance of Acidobacteria, Chloroflexi and Alphaproteobacteria was higher in near‐surface layers, while the relative abundance of Actinobacteria, Gemmatimonadetes and Betaproteobacteria was higher in the subsurface samples. The microbial community structure was distinct between the surface and subsurface soil layers, strongly correlating with variation in total carbon (TC) and carbon to nitrogen ratio (C/N). The differences in the microbial community between the layers were about the same as the horizontal differences between sites separated by many kilometers. Overall, we found that TC and C/N were the best predictors for both surface and subsurface microbial community distribution. Exploration of the relative contribution of distance and environmental variables to community composition suggests that the contemporary environment is the primary driver of microbial distribution in this region. Reflecting niche conservatism in evolution, the microbial communities in each soil site and layer tended to be more phylogenetically clustered than expected by chance, and surface soil layer samples were more likely to be clustered than subsurface samples.

Bridge life cycle assessment with data uncertainty - Yu-Rong Zhang; Wen-Jie Wu; Yuan-Feng Wang (The International Journal of Life Cycle Assessment, 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Impact of urban land-use change in eastern China on the East Asian subtropical monsoon: A numerical study - Rong Yu; Zhihong Jiang; Panmao Zhai (Journal of Meteorological Research, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Distribution and contamination assessment of heavy metals in soils from tidal flat, oil exploitation zone and restored wetland in the Yellow River Estuary - Xinying Yao; Rong Xiao; Ziwen Ma; Ying Xie; Mingxiang Zhang; Feihai Yu (Wetlands, 2016)

Isolation and characterization of the marine algicidal bacterium Pseudoalteromonas S1 against the harmful alga Akashiwo sanguinea - Hong-Ye Sun; Yu Zhang; Hui-Rong Chen; Chang-Xing Hu; Hui Li; Zhang-Li Hu (Marine Biology, 2016)

Heavy metal distribution in different soil aggregate size classes from restored brackish marsh, oil exploitation zone, and tidal mud flat of the Yellow River Delta - Rong Xiao; Mingxiang Zhang; Xinying Yao; Ziwen Ma; Feihai Yu; Junhong Bai (Journal of Soils and Sediments, 2016)

An observation-based progression modeling approach to spring and autumn deciduous tree phenology - Rong Yu; Mark D. Schwartz; Alison Donnelly; Liang Liang (International Journal of Biometeorology, 2016)

Element distribution over the surface of fish scales and its connection to the geochemical environment of habitats: a potential biogeochemical tag - TsingHai Wang; Yan-Chen Lai; Chia-Che Chiang; Yu-Rong Cheng; Yi-Kong Hsieh; Chu-Fang Wang (Environmental Monitoring and Assessment, 2016)

Selenium and Iodine Levels in Subjects with Kashin-Beck Disease: a Meta-analysis - Lei Yang; Guang-hui Zhao; Fang-fang Yu; Rong-qiang Zhang; Xiong Guo (Biological Trace Element Research, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Assessment of interannual sea surface salinity variability and its effects on the barrier layer in the equatorial Pacific using BNU-ESM - Hai Zhi; Rong-Hua Zhang; Fei Zheng; Pengfei Lin; Lanning Wang; Peng Yu (Advances in Atmospheric Sciences, 2016)

Chemical composition, antioxidant and antimicrobial activity of the essential oil from the leaves of Macleaya cordata (Willd) R. Br. - Chun-Mei Li; Xiao-Yong Yang; Yi-Rong Zhong; Jian-Ping Yu (Natural Product Research, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

Effect of long-term industrial waste effluent pollution on soil enzyme activities and bacterial community composition - Gangavarapu Subrahmanyam; Ju-Pei Shen; Yu-Rong Liu; Gattupalli Archana; Li-Mei Zhang (Environmental Monitoring and Assessment, 2016)

Pantoea pleuroti sp. nov., Isolated from the Fruiting Bodies of Pleurotus eryngii - Yuanwei Ma; Yonggang Yin; Chengbo Rong; Sanfeng Chen; Yu Liu; Shouxian Wang; Feng Xu (Current Microbiology, 2016)

The meso-mechanism study of gypsum rock weakening in brine solutions - Wei Dong Yu; Wei Guo Liang; Yan Rong Li; Yan Mei Yu (Bulletin of Engineering Geology and the Environment, 2016)

Connectivity-Based Brain Parcellation - Qi Wang; Rong Chen; Joseph JaJa; Yu Jin; L. Elliot Hong; Edward H. Herskovits (Neuroinformatics, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)